DFT Study on the Reaction Mechanism of Cyclization of 2-Hydroxy Chalcone Catalyzed by Bronsted Acid with M06-2X Functional - Suci Zulaikha Hildayani; Muhamad Abdulkadir Martoprawiro; Yana Maolana Syah (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
Flavanones are one of the flavonoid group that has wide variety of applications such as a precursors in drug discovery. In the laboratory, flavanone is often synthesized from chalcone compounds. The conversion of chalcone to flavanone can be catalyzed by bronsted acid. The reaction mechanism for this process is proposed through the Michael addition reaction, however, the energetic details and the rate determining step for this reaction is not certainly known. This research aimed to investigate the reaction mechanism for chalcone-flavanone conversion with the present of bronsted acid as catalyst and also studied the effect of the solvent on the reaction energy profile with computational method. In this study, the modeling of the reaction mechanism for the said reaction was carried out using the DFT computational method with M06-2X functional. The computation was done both in the gas phase and in present of the solvent effect using the PCM models. The results showed that the mechanism of chalcone-flavanone conversion occurred in three steps which are protonation, cyclization, and then tautomerization. Based on these calculations, the rate determining step was the tautomerization reaction, which exhibited the same results with or without the solvent effects. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).